Avaliação da tensão formada na região periimplantar após a instalação de próteses parciais fixas parafusadas e cimentadas - Oliveira, José Luiz Góes de (2013)
Passivity fit of an implant fixed partial denture (FPD) is one of major factor in treatment success. Among various factors that influence the passive fit of a prostheses is the kind of retained. Thus, the aim of this study was to evaluate, with the aid of linear strain gages (gauges), the tension generated around two implants after installation of a three-unit implant FPD. Five groups were analyzed (n = 5): 1. Control (only the abutments on implants); 2. Cement-retained prosthesis; 3. Screw-retained prosthesis made from plastic cylinders; 4. Screw-retained prosthesis made from Co-Cr machined collar abutments; 5. Hybrid prosthesis (cemented / screwed). For the investigation, homogeneous polyurethane experimental model with two parallel external hexagon implants was used. From this model, transfer impression and one master stone cast was made on which all frameworks were made accompanying a wax pattern. Aiming to measure the tensions, four strain gauges for each implant placed in the mesial, distal, buccal and lingual were glued on the top surface of the experimental block. The tests were performed by installing the samples on the implants according to the characteristics of each group. Five repetitions of readings for each specimen were performed. One-way ANOVA and Tukey test were applied to the average values (p <.05). The mean and standard deviation were obtained: Group 1 (48.71 με ± 0.29), Group 2 (60.03 με ± 22.65) and group 3 (254.15 με ± 46.23), Group 4 (215,42 με ± 30.48), Group 5 (70.05 με ± 13.78). These results showed that the cement-retained prostheses have the ability to produce less stress on the peri-implant area when compared to the screw-retained prosthesis (p≤.05). It was observed that the hybrid group had similar performance to the cement-retained prostheses and the control group (p>.05). Furthermore, the screw-retained prosthesis made from plastic cylinders showed similar performance to the Co-Cr machined collar abutments (p>.05). Finally, these results demonstrated that the generated tension to the peri-implant tissues is directly related to the type of retention.